The use of leniency policies in the prosecution of cartels and organized crime : underlying principles and judicial practice - Mendes, Francisco Schertel Ferreira (2019)
Tese (doutorado) — Universidade de Brasília, Faculdade de Direito, Programa de Pós-Graduação em Direito, 2019.